2015
DOI: 10.1007/s10897-015-9863-3
|View full text |Cite
|
Sign up to set email alerts
|

Portrait of the Master Genetic Counselor Clinician: A Qualitative Investigation of Expertise in Genetic Counseling

Abstract: This study comprises an initial empirical description of personal and professional characteristics of master genetic counselors-those considered to be experts in the profession. Fifteen peer-nominated genetic counselors, actively engaged in providing clinical services to patients, participated in semi-structured telephone interviews exploring their personal qualities, inspirations, and perspectives on professional development of expertise. Analysis using modified Consensual Qualitative Research methods yielded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…With respect to the larger community, they accessed these individuals either through the NSGC or a local association. These findings are consistent with previous genetic counseling research where genetic counselors identified colleagues as a ‘highly valued’ resource (Miranda, McCarthy Veach, Martyr, & LeRoy, ; Zahm et al, ). Research in other professional fields such as nursing and occupational therapy also found that support and guidance from more experienced professionals and other staff members comprised a critical component of recent graduates’ transitional experience (Toal‐Sullivan, ; Valdez, ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…With respect to the larger community, they accessed these individuals either through the NSGC or a local association. These findings are consistent with previous genetic counseling research where genetic counselors identified colleagues as a ‘highly valued’ resource (Miranda, McCarthy Veach, Martyr, & LeRoy, ; Zahm et al, ). Research in other professional fields such as nursing and occupational therapy also found that support and guidance from more experienced professionals and other staff members comprised a critical component of recent graduates’ transitional experience (Toal‐Sullivan, ; Valdez, ).…”
Section: Discussionsupporting
confidence: 90%
“…With respect to the larger community, they accessed these individuals either through the NSGC or a local association. These findings are consistent with previous genetic counseling research where genetic counselors identified colleagues as a 'highly valued' resource (Miranda, McCarthy Veach, Martyr, & LeRoy, 2016;Zahm et al, 2016). Other strategies used to address professional challenges included attending and presenting in professional groups.…”
Section: Participant Strategiessupporting
confidence: 88%
“…As these papers attest, genetic counselors should remain alert and open to the ways they can challenge themselves professionally. These growth-invoking challenges may be subtle or embedded within personal experiences (Colón 2016;Disco 2016), professional characteristics (Miranda et al 2016), patients' stories (Wells et al 2016;Spencer 2016); or career journeys . Alternatively, the opportunities could be more blatant: creating new training opportunities (Atzinger et al 2016;Wiesman et al 2016), training models (Baty et al 2016), or career ladders within large hospital structure (Kofman et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic counselors routinely engage with patients and family members who are grappling with larger questions of meaning while also making decisions regarding their genetic risk (Biesecker 2001), and they appear to learn a great deal about themselves in the process (Runyon et al 2010). Their experiences may promote positive professional development in the form of enhanced empathy, strengthened self-esteem, improvement of clinical skills, and development of expertise (Miranda et al 2015;Runyon et al 2010;Zahn et al in review). Their experiences may also result in negative outcomes such as burnout and compassion fatigue (e.g., Injeyan et al 2011;Lee et al 2014;Udipi et al 2008).…”
Section: Issues Of Meaning In Genetic Counselor Professional Developmmentioning
confidence: 99%
“…Despite a growing body of literature on genetic counselor professional development (e.g., Abrams and Kessler 2002;Kessler 1992;McCarthy Veach et al 2002;McCarthy Veach and LeRoy 2012;Resta 2002;Miranda et al 2015;Runyon et al 2010;Zahm et al 2015), no empirical research has explicitly and comprehensively investigated the extent to which genetic counselors experience their own sense of meaning and how this meaning has been shaped over time. More specifically, data are lacking about how genetic counselors develop their sense of meaning prior to working within the field and how they both experience and express this meaning in their work.…”
mentioning
confidence: 99%